Forward Electric Stimulation-Induced Interference in Intracochlear Electrocochleography of Acoustic Stimulation in the Cochlea of Guinea Pigs - Min, Shiyao; Lu, Tianhao; Chen, Min; Mao, Jiabao; Hu, Xuerui; Li, Shufeng (Frontiers in Neuroscience, 2022)
Electric-acoustic stimulation (EAS) uses amplified sound by a hearing aid to stimulate an apical low-frequency region of the cochlea and electrical current from a cochlear implant (CI) to stimulate the basal high-frequency region. EAS recipients had significantly improved speech perception, music appreciation, and hearing function in noise compared to those relying on CI electrical stimulation (ES) alone. However, the interaction between basal ES and apical acoustic stimulation (AS) in the cochlea potentially affects EAS advantages. To investigate ES-AS interaction, we designed a system that recorded the electrically evoked compound action potential (ECAP) and the auditory evoked potential (AEP). We used an intracochlear electrode array to deliver ES at the basal cochlea and detect intracochlear electrocochleography (iECochG) generated from apical AS. Within iECochG, 3 or 6 dB (double or quadruple intensity of ECAP threshold) electric stimulation, 1 ms-forward ES significantly increased CAP amplitudes of 4 kHz/20 dB AS compared to 0 dB ES. Notably, 1 ms-forward 3 dB ES significantly increased CAP amplitudes of 4 kHz/20 dB AS, while 3 or 5 ms-forward ES did not change the CAP amplitudes. The elevation in CAP amplitude of 40 dB/4 kHz AS induced by 1 ms-forward 3 dB ES was significantly lower than that in 20 dB/4 kHz AS. With 1 ms-forward 3 dB ES, AS frequency and stimulating electrode location have no significant impact on relative CAP amplitudes of 20 dB AS. These results suggest that the basal forward ES and the following apical AS could produce a cumulative effect on the auditory nerve response.